2017
DOI: 10.1007/s11999-016-4836-x
|View full text |Cite
|
Sign up to set email alerts
|

Length of Endoprosthetic Reconstruction in Revision Knee Arthroplasty Is Associated With Complications and Reoperations

Abstract: Background Complex revision total knee arthroplasty (TKA) often calls for endoprosthetic reconstruction to address bone loss, poor bone quality, and soft tissue insufficiency. Larger amounts of segmental bone loss in the setting of joint replacement may be associated with greater areas of devascularized tissue, which could increase the risk of complications and worsen functional results. Questions/purposes Are longer endoprosthetic reconstructions associated with (1) higher risk of deep infection; (2) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Similarly, Holl et al 56 identified a high incidence of complications in 11 out of 20 patients who underwent the placement of this type of implant, however without the need for amputation. These results were corroborated by Barry et al, 57 who demonstrated a high number of complications and reoperations with this treatment, although, according to the authors, it is a viable option for salvage of the limb.…”
Section: Non-conventional Prostheses and Customized Mega Prosthesessupporting
confidence: 59%
“…Similarly, Holl et al 56 identified a high incidence of complications in 11 out of 20 patients who underwent the placement of this type of implant, however without the need for amputation. These results were corroborated by Barry et al, 57 who demonstrated a high number of complications and reoperations with this treatment, although, according to the authors, it is a viable option for salvage of the limb.…”
Section: Non-conventional Prostheses and Customized Mega Prosthesessupporting
confidence: 59%
“…However, the modularity of these systems was not sufficient to prevent local complications such as infection, periprosthetic fracture or extensor rupture. 32…”
Section: Outcomes Of Hinged Implants In Tka Revision (Table 1)mentioning
confidence: 99%
“…The increased infection rates in knees with more complex revision procedures is also supported by Barry et al who reported a correlation of the extend of the surgery and the risk for infection in revision TKA (10). Previous studies have also shown a high deep implant infection rate (56%) in hinged TKAs (11).…”
mentioning
confidence: 74%